2010
DOI: 10.2134/jeq2009.0130
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Urea Fertilizer Placement on Nitrous Oxide Production from a Silt Loam Soil

Abstract: Urea placement in band or nests has been shown to enhance N use efficiency, but limited work has been done to assess its affect on N(2)O emissions. This study compared N(2)O emissions from urea prills applied to an Amsterdam silt loam (fine-silty, mixed, superactive, frigid Typic Haplustolls) using broadcast, band, and nest placements. Experiments were conducted in greenhouse pots (200 kg N ha(-1)) and in canola (Brassica rapa L.) seeded fields using rates of 100 kg N ha(-1) (recommended) and 200 kg N ha(-1). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
49
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 22 publications
(25 reference statements)
7
49
0
4
Order By: Relevance
“…Burton et al (2008a) also reported no impact of double midrow-banding to increase N 2 O emissions from fertilizers applied at the same rate (80 kg ha -1 ) as in the current study. In contrast, other studies (Engel et al, 2010;Maharjan and Venterea, 2013) used higher rates (180-200 kg ha -1 ) in studies simulating siderow-banding by hand trenching compared to those done in the northern Great Plains in Canada and found greater N 2 O emissions compared to broadcast incorporation. Beside the method of band placement, the differing effect of banding on emissions between studies could be due to a higher N rate per area increasing emissions within bands.…”
Section: Fertilizer Placement Effectmentioning
confidence: 92%
See 1 more Smart Citation
“…Burton et al (2008a) also reported no impact of double midrow-banding to increase N 2 O emissions from fertilizers applied at the same rate (80 kg ha -1 ) as in the current study. In contrast, other studies (Engel et al, 2010;Maharjan and Venterea, 2013) used higher rates (180-200 kg ha -1 ) in studies simulating siderow-banding by hand trenching compared to those done in the northern Great Plains in Canada and found greater N 2 O emissions compared to broadcast incorporation. Beside the method of band placement, the differing effect of banding on emissions between studies could be due to a higher N rate per area increasing emissions within bands.…”
Section: Fertilizer Placement Effectmentioning
confidence: 92%
“…Surface side-banding of N fertilizers increased N 2 O emissions compared to surface-broadcast at an irrigated grain corn site in Central Great Plains of Colorado (Halvorson and Del Grosso, 2013). Hand-trenching using a hoe to simulated banding of urea delayed and increased N 2 O emissions compared to surface-broadcast under canola at a site in Montana (Engel et al, 2010). Single midrow-banding (banding between all rows) also by hand-trenching using a hoe, doubled N 2 O emissions compared to broadcast-incorporation of urea applied at 180 kg ha -1 to a corn site in Minnesota (Maharjan and Venterea, 2013).…”
mentioning
confidence: 99%
“…Some existing experimental and modeling studies in eastern Washington State and southwest Montana have found N 2 O emissions, as a percentage of nitrogen applied, that are lower than the current Intergovernmental Panel on Climate Change (IPCC) benchmark of 1% (0.1-0.9%; Cochran et al, 1981;Dusenbury et al, 2008;Haile-Mariam et al, 2008;Engel et al, 2010). However, other inland Northwest studies suggest emissions are more in line with, or even notably above, the IPCC benchmark (1.1-4.4%; Halvorson, 2010;Stöckle et al, 2012;Waldo, 2016).…”
Section: Climate Mitigation Opportunitiesmentioning
confidence: 88%
“…Dari total pupuk urea yang diberikan kepada tanaman, hanya 50% yang dapat diserap oleh tanaman, sedangkan sisanya hilang karena tercuci maupun menguap ke udara (de Datta 1981). Emisi gas N 2 O dari lahan sawah meningkat dengan semakin tingginya takaran pupuk N (Engel et al 2010;Weller et al 2015). Pembentukan N 2 O dipicu oleh kondisi hara N yang berlebihan di dalam tanah pada kondisi tidak jenuh air (Sander et al 2014).…”
Section: Hubungan Skala Bwd Dan Lingkunganunclassified